Amyloidosis with recurrent oral and peptic ulcers mimicking Behcet's syndrome: A case report. Issue 1 (22nd February 2022) - Peng, Jiajing; Liu, Tian
Abstract: Introduction: Amyloidosis and Behcet's syndrome (BS) are systemic diseases that affect multiple systems. Similar mucocutaneous damage occurs in amyloidosis and BS, thus causing a delayed or incorrect diagnosis. The prognosis of patients with amyloidosis is poor. Therefore, exclusion of other diagnoses is important before confirming the presence of BS. Case Report: We report a case of a 43‐year‐old woman who initially presented with peptic ulcers, recurrent oral ulcers, and suspicious genital ulcers resembling BS. She was treated with systemic steroids at the local hospital for approximately 2 years. However, her symptoms were not relieved, and the gradual presence of macroglossia, hoarseness, periorbital purpura, proteinuria, and cardiac involvement strongly suggested amyloidosis. She was diagnosed with immunoglobulin light chain amyloidosis (lambda type) after extensive examinations, including an elevated monoclonal protein concentration, Congo red staining, and immunohistochemical staining of abdominal fat. She was then treated with a chemotherapy regimen (melphalan and dexamethasone). Conclusion: Recurrent oral ulcers can be the first manifestation of amyloidosis. The diagnosis of BS requires the exclusion of other diseases, and amyloidosis should be considered as a differential diagnosis. Key points: Sometimes amyloidosis mimics Behcet's syndrome (BS). When the patient's symptoms can not be relieved by systemic steroids, rheumatologists should reconfirm the diagnosis of BS. When the diagnosis is unclear, multiple biopsies are required. Abstract : We report a case of a 43‐year‐old woman who initially presented with peptic ulcers, recurrent oral ulcers, and suspicious genital ulcers resembling Behcet's syndrome. Her symptoms were not relieved by systemic steroids and gradually presented multiple system damage involving kidney, heart, lung, skin, and mucous membranes. She was diagnosed with systemic immunoglobulin light chain (AL)  amyloidosis after three biopsies.